THE PREVALENCE OF LOW BACK PAIN AND ASSOCIATED RISK FACTORS AMONGST UNDERGRADUATE MEDICAL IMAGING STUDENTS AT THE INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA (IIUM) KUANTAN - ZAINUDDIN, NUR FAKHIRA; SOO FOON, MOEY; MOHD NOOR, NUR EMELIYA NATASHA (International Journal of Allied Health Sciences, 2022)
Introduction: University students are at risk of developing low back pain (LBP) because of the curriculum task load that lead them to practice a sedentary lifestyle. This study aims to determine the prevalence of LBP and its associated risk factors among the Medical Imaging undergraduate students at the International Islamic University Malaysia (IIUM), Kuantan. Methods: Ninety-two respondents were randomly selected for the study. Data was collected using a self-constructed questionnaire with content and reliability validation. The Statistical Package for Social Science (SPSS) Version 26 was used to analyze the data. Results: The findings showed that 72% of the respondents have LBP once in their lifetime. Fatigue and body posture were found to be the most associated risk factors of LBP (p=0.001 and p=0.02) respectively. A significant difference between the respondents’ year of study and the prevalence of LBP (p=0.037) was also indicated. Conclusion: The prevalence of LBP among the university student was relatively high, possibly due to the curriculum task load that resulted in long study hours and a sedentary lifestyle that could lead them to be fatigue and possess poor body postures. Furthermore, it could indirectly pose increased risk of developing LBP. A significant difference between the respondent’s year of study and the prevalence of LBP could be due to the increased task load, stress and clinical posting accumulated throughout the years of studying. As such, higher learning institutions should create awareness to reduce the prevalence of LBP and its effect on the well-being their students.